Maize Seedling Establishment, Grain Yield and Crop Water Productivity Response to Seed Priming and Irrigation Management in a Mediterranean Arid Environment - AbdAllah M. El-Sanatawy; Ahmed S. M. El-Kholy; Mohamed M. A. Ali; Mohamed F. Awad; Elsayed Mansour (Agronomy, 2021)
Water shortage is a major environmental stress that destructively impacts maize production, particularly in arid regions. Therefore, improving irrigation management and increasing productivity per unit of water applied are needed, especially under the rising temperature and precipitation fluctuations induced by climate change. Laboratory and field trials were carried out in the present study, which were aimed at assessing the possibility of promoting maize germination, growth, grain yield and crop water productivity (CWP) using seed priming under different irrigation regimes. Two seed priming treatments, i.e., hydro-priming and hardening versus unprimed seeds, were applied under four irrigation regimes, i.e., 120, 100, 80 and 60% of estimated crop evapotranspiration (ETc). The obtained results indicated that increasing irrigation water from 100% up to 120% ETc did not significantly increase grain yield or contributing traits, while it decreased CWP. Deficit irrigation of 80 and 60% ETc gradually decreased grain yield and all attributed traits. Seed priming significantly ameliorated seedlings’ vigor as indicated by earlier germination, higher germination percentage, longer roots and shoots, and heavier fresh and dry weight than unprimed seeds with the superiority of hardening treatment. Additionally, under field conditions, seed priming significantly increased grain yield, yield contributing traits and CWP compared with unprimed treatment. Interestingly, the results reflect the role of seed priming, particularly hardening, in mitigating negative impacts of drought stress and enhancing maize growth, grain yield and attributed traits as well as CWP under deficit irrigation conditions. This was demonstrated by a significant increase in grain yield and CWP under moderate drought and severe drought conditions compared with unprimed treatment. These results highlight that efficient irrigation management and seed priming can increase maize yield and water productivity in arid environments.